Persistence of hyperinvasive meningococcal strain types during global spread as recorded in the PubMLST database - Watkins, E; Maiden, M (Public Library of Science, 2012)
Neisseria meningitidis is a major cause of septicaemia and meningitis worldwide. Most disease in Europe, the Americas and Australasia is caused by meningococci expressing serogroup B capsules, but no vaccine against this polysaccharide exists. Potential candidates for 'serogroup B substitute' vaccines are outer membrane protein antigens including the typing antigens PorA and FetA. The web-accessible PubMLST database (www.pubmlst.org) was used to investigate the temporal and geographical patterns of associations among PorA and FetA protein variants and lineages defined by combinations of housekeeping genes, known as clonal complexes. The sample contained 3460 isolates with genotypic information from 57 countries over a 74 year period. Although shifting associations among antigen variants and clonal complexes were evident, a subset of strain types associated with several serogroups persisted for decades and proliferated globally. Genetic stability among outer membrane proteins of serogroup A meningococci has been described previously, but here long-lived genetic associations were also observed among meningococci belonging to serogroups B and C. The patterns of variation were consistent with behaviour predicted by models that invoke inter-strain competition mediated by immune selection. There was also substantial geographic and temporal heterogeneity in antigenic repertoires, providing both opportunities and challenges for the design of broad coverage protein-based meningococcal vaccines.